Preparation of electrospun small intestinal submucosa/poly(Caprolactone‐co‐lactide‐co‐glycolide) nanofiber sheet as a potential drug carrier - Thao, Nguyen Thi Thu; Lee, Surha; Shin, Gi Ru; Kang, Youngji; Choi, Sangdun; Kim, Moon Suk (Pharmaceutics, 2021)
In this work, we chose small intestine submucosa (SIS) as a drug carrier because SIS possesses good biocompatibility, non‐immunogenic property and bio‐resorbability, and performed electrospinning for preparation of nanofiber sheets (NS). For the preparation of drug‐loaded electrospun SIS nanofiber sheets as a drug carrier, we used poly(ε‐caprolactone‐ran‐L‐lactide) (PCLA) copolymers to improve the electrospinning performance of SIS. The electrospinning of SIS and PCLA provided the electrospun SIS/PCLA (S/P)‐nanofiber sheet (S/P‐NS) with adjustable thickness and areas. The electrospun S/P‐NS showed different porosities, pore sizes, diameters and tensile strengths depending on the ratios between SIS and PCLA. The electrospun S/P‐NS was used as a drug carrier of the dexamethasone (Dex) and silver sulfadiazine (AgS) drug related to anti-inflammation. Dex‐loaded S/P‐NS and AgS‐loaded S/P‐NS was successfully fabricated by the electrospinning. In the in vitro and in vivo release, we successfully confirmed the possibility for the sustained release of Dex and AgS from the Dex‐S/P‐NS and AgS‐S/P‐NS for three weeks. In addition, the sustained Dex and AgS release suppressed the macrophage infiltration. Collectively, we achieved feasible development of SIS nanofiber sheets for a sustained Dex and AgS delivery system.
Keywords: Drug; Electrospinning; Nanofiber sheets; Small intestine submucosa; Sustained delivery